2018
DOI: 10.17221/272/2017-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agri-food products: A review of consumer preference studies through experimental economics

Abstract: In the last few decades, the interest of consumers towards sustainable agri-food products has been growing. This trend reflects changes in the consumption patterns, which have been deeply influenced by the increased sensitivity concerning social and environmental issues. In this sense, several studies, with different methodological approaches, have investigated consumers’ willingness to pay and its determinants for products with different sustainability labels. To systematise the obtained results, this paper o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…In total, only 12% of the respondents were willing to pay a premium of 10% or more. As a result of a literature review, Checchini et al [65] concluded that (based on the given examined sources), "local" production generally had less impact on consumers' willingness to pay. Although few studies deal with comparative examinations on willingness to pay for different local products, experience shows that consumers' willingness to pay also varies from product to product.…”
Section: +11%mentioning
confidence: 99%
“…In total, only 12% of the respondents were willing to pay a premium of 10% or more. As a result of a literature review, Checchini et al [65] concluded that (based on the given examined sources), "local" production generally had less impact on consumers' willingness to pay. Although few studies deal with comparative examinations on willingness to pay for different local products, experience shows that consumers' willingness to pay also varies from product to product.…”
Section: +11%mentioning
confidence: 99%
“…Several studies (Akaichi et al, 2016;Cecchini et al, 2018;Polenzani et al, 2020) underlined the demand for locally produced food is increasing due to consumers' growing attention towards environmental and social sustainability: these results suggest that the use of environmental information labels could be a product differentiation mechanism and generate more support for sustainable companies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on supply chains have recently focused on sustainability issues in response to the growing concern for the environmental impact of food supply chains (Training and Research Institute for Transport [isfort in Italian], 2013; Cicatiello et al, 2012b). This growing consumer environmental attention results in an increase in the demand for locally produced food that is considered safer for health, and towards more social and environmental sustainability (Akaichi et al, 2016;Cecchini et al, 2018;Polenzani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…FT products are nowadays readily available in Europe, the United States, and Canada, where there is a large and growing number of consumers willing to pay a higher price for goods with FT certification (Cecchini et al, 2018; Robbins, 2013; Verhoef & van Doorn, 2016). The entire FT system is managed in a very participatory way, and it can be considered a network of networks that link their stakeholders with consumers all over the world.…”
Section: Introductionmentioning
confidence: 99%